DISTRIBUSI VERTIKAL OSTRACODA DAN HUBUNGANNYA DENGAN PERUBAHAN LINGKUNGAN DI PERAIRAN TELUK JAKARTA - -, Lili Fauzielly (Bulletin of Scientific Contribution, 2013)
A vertical distributions from quantitative analysis of ostracods and Total Organic carbon (TOC) was recorded from short sediment core from inner part of Jakarta Bay. A total of 56 ostracod species were obtained from 9 core samples. The dominant species were Keijella carriei and Loxoconcha wrighti, which are common in areas with high TOC and TN contents. According to analysis of ostracod assemblages and CNS analysis, the site began to be influenced by organic contamination from around 1950. Although the population of Jakarta City has increased rapidly since then, TOC and TN contents which were low, have gradually increased (0.58%–0.9%). The increased sedimentation rate after 1950 resulted in an increasing TOC ratio.